Transformation of Flat File into Data Warehouse (Global Journal of Computer Science and Technology, 2011)
A Flat file Semi Structured Data comes from different sources or operational systems for storage in the data warehouse Extraction transformation and loading of the data could be necessary Moreover input flat file data must be transformed into a uniform format which could be more suitable for analytical purposes Aim of this research is to analysis the delimiters of the flat file to transform flat file into uniform format and suggest a suitable algorithm for implementation such type of algorithm could be solve the problem of transformation of the flat file data and such algorithm could be useful for extraction transformation and loading of huge amount of flat file data into data warehouse